Implementasi Perlindungan Hukum Hak Kekayaan Intelektual (HKI) Terhadap Ekspresi Budaya Tradisional (EBT) Di Tinjau Dari UU Nomor 28 Tahun 2014 Tentang Hak Cipta - Putu Nendrawan; Gede Rastika (Universitas Pendidikan Ganesha, 2021)
The purpose of this research is to find out how the current intellectual property rights (IPR) protection which regulates Traditional Cultural Expression (EBT). The research approach method used in this study is a juridical empirical method with descriptive analytical specifications. The results of the study found that Traditional Cultural Expressions (EBT) need protection of Intellectual Property Rights (HKI). The government's efforts to protect Traditional Cultural Expressions (EBT) can be carried out by implementing appropriate and proper protection regulations for Traditional Cultural Expressions. The importance of implementing proper and good regulations with the aim of protecting in the future Traditional Cultural Expressions do not experience extinction at both the regional and national levels.